International inventor teams and technological variety in multinational enterprises - Giacomo Damioli; Björn Jindra; Annette Kristiansen (The Journal of Technology Transfer, 2023)
This study investigates the relationship between international inventor teams and the technological variety of multinational enterprises. We frame this relationship conceptually by considering two possible attributes of diversity in international inventor teams: cultural differences and heterogeneous knowledge. We employ a dataset for 454 multinational enterprises with 71,126 subsidiaries across 185 countries that applied for 139,066 priority patents during the period 2007–2014. Fixed-effects panel estimations indicate that international inventor teams are positively associated with both related and unrelated technological variety at the level of the MNE. Such relationships display diminishing marginal returns, pointing to management and coordination costs reducing the benefits from international inventor teams. In addition, we find that MNEs with higher technological innovation capability deal with the additional complexity from managing and coordinating international inventor teams by consolidating technological variety.
Keywords: O32; F23; O14; 600; Multinational enterprise; Inventor team; Technological variety; Knowledge sourcing; Knowledge recombination